TEACHING PROFESSION IN CONSTRUCTION: EXPECTATIONS AND CONFLICT TO BE A TEACHER - Gomes, Alberto Albuquerque [UNESP] (Univ Federal Mato Grosso Sul, 2016)
To understand the context where we teach, considering new demands, the pressure suffered for teachers to redefine their roles, tasks and identities, we conducted an investigation with ex-students ( just graduated from Pedagogy) from a Brazilian public university, that are teachers at least for two years on the Municipal Education System in Presidente Prudente, Sao Paulo State, Brazil. We try to demonstrate, in this article forms to insert those teachers in the world of work and how important and fundamental it is to strengthening identities. We also analysed how the lost of authonomy, the difficulties on relationship between teacher/student/parents of student can undermine this identity.
Keywords: Identity; Profession; Teaching Pedagogy